2020
DOI: 10.1371/journal.pone.0235346
|View full text |Cite
|
Sign up to set email alerts
|

Heightened affective response to perturbation of respiratory but not pain signals in eating, mood, and anxiety disorders

Abstract: Several studies have recently suggested that an abnormal processing of respiratory interoceptive and nociceptive (painful) stimuli may contribute to eating disorder (ED) pathophysiology. Mood and anxiety disorders (MA) are also characterized by abnormal respiratory symptoms, and show substantial comorbidity with ED. However, no studies have examined both respiratory and pain processing simultaneously within ED and MA. The present study systematically evaluated responses to perturbations of respiratory and noci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 84 publications
3
15
0
Order By: Relevance
“…Several auxiliary analyses were performed to corroborate these finding: In short, no pre-or post-treatment group differences in baseline HR were detected and results were replicated when the repeating the analysis with all participants tested, and (s. Supplementary Results, Table S7). Of note, there was no appreciable relationship between pre-treatment peak CPT HR-response and %AUPC (see: Figure S4) suggesting that peak CPT HR-response are not a surrogate marker of pain, replicating previous findings 28,29 . .…”
Section: Secondary Outcome Ii: Adverse Effectssupporting
confidence: 81%
“…Several auxiliary analyses were performed to corroborate these finding: In short, no pre-or post-treatment group differences in baseline HR were detected and results were replicated when the repeating the analysis with all participants tested, and (s. Supplementary Results, Table S7). Of note, there was no appreciable relationship between pre-treatment peak CPT HR-response and %AUPC (see: Figure S4) suggesting that peak CPT HR-response are not a surrogate marker of pain, replicating previous findings 28,29 . .…”
Section: Secondary Outcome Ii: Adverse Effectssupporting
confidence: 81%
“…This model had an acceptable fit (χ 2 (736) = 1094.002, p < 0.001; CFI = 0.969, TLI = 0.961, RMSEA = 0.027 (0.024; 0.030)), but it did not show evidence of approximated simple structure, as there were three items with loadings whose confidence interval was entirely over 0.32 on two factors, and there were two factors on which loaded only two items (see Table S2 in the SM). In the final model, the first factor (BPQ-BOA) was loaded by body awareness items (15,18,16,17,12,19,5) and the third factor (BPQ-SUP) by supradiaphragmatic reactivity items (32,27,33,28,39,37,38,34). The second factor (BPQ-BOA/SUB) comprised some items from the body awareness scale and some from the subdiaphragmatic reactivity scale (45,42,14,44,13,46,7), but all tapping into bloating and digestive issues.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, postural orthostatic tachycardia syndrome patients often exhibit mild to moderate depression and anxiety disorders symptoms [ 5 ] as well as vasovagal syncope patients [ 6 ]. Though the underlying mechanisms behind this association include genetic risks, autonomic nervous system (ANS) dysfunction, increased exteroceptive and interoceptive mechanisms and decreased proprioception have been associated with anxiety [ 7 , 8 ], depression [ 9 , 10 ], post-traumatic stress [ 11 ], autism [ 12 , 13 ], schizophrenia [ 14 ], eating disorders [ 15 , 16 ] and in adults with hypertension [ 17 ]. Though interoception, or the process of sensing, interpreting and integrating internal bodily signals, has been linked to various clinical conditions and several randomized controlled trials found that interventions with interoception were effective in ameliorating symptoms related to anxiety disorders, eating disorders, psychosomatic disorders, and addictive disorders that also encompassed improvements of interoceptive measurements, measures self-reporting ameliorating symptoms are often related to specific illness symptoms only.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the ASI assesses a more general predisposition to anxiety over bodily sensations and focuses predominantly on cardiac and respiratory sensations. Given new data suggesting that individuals with EDs endorse heightened affective responses to respiratory signals (Lapidus et al, 2020), future research may benefit from exploring the relative contribution of general (ASI‐3) and GI‐specific anxiety sensitivity (VSI) on different aspects of ED psychopathology. In sum, data from our sample of treatment‐seeking individuals with EDs provide initial psychometric support for use of the VSI in this population.…”
Section: Discussionmentioning
confidence: 99%